PENGARUH PEMBERIAN KOMPRES PANAS TERHADAP PENURUNAN SKALA NYERI PADA IBU PRIMIPARA POST SEKSIO SESARIA - Diana Putri, Diana Putri; Desi Maria, Rulfia (Jurnal Kesehatan - STIKes Prima Nusantara, 2015)
Caesarean section is spending the fetus through the abdominal wall incision and the uterine wall. During the post-operation period, the treatment process is directed to re-establish the patient's physiological balance and reduce pain. One non pharmacologic pain management is by using hot compress. This research aims to determine the effect of a hot compress to decrease pain scale in primipara mothers post cesarean section as non-pharmacological measures. This form of this research is analytic with pre-experimental design with one group pretest-posttest design. The population in this research is a post SC primipara mothers were being treated at Ibnu Sina Islamic hospital in Bukittinggi in 2014. Samples numbered 34 people with a sampling technique that concecutive sampling. By using a pain scale measurement sheet first interview (pretest) and the questionnaires measuring pain scale (posttest) after being given a hot compress for 20 minutes. Data were analyzed by using T test dependent. Most of respondents have moderate category 21 respondents (61.76%) before being given a hot compress and the weight category 13 respondents (38.24%) and after being given the hot compress is largely in the category 27 respondents (79.41%) no respondents in the weight category. Results showed that there is an effect on the pain scale decline in post-cesarean primipara mothers before and after application of hot (P = 0.000). Being expected to whole health workers are able to implement hot compress in doing pain management especially to post primipara mothers.